Authority and freedom (Polis (Santiago), 2018)
The author explains how from growing rebellion against authority in the last four centuries, there has been a social philosophy which criticizes the idea of any authoritarian control, and that it thus poses  the great intellectual problem of the demarcation of two separate spheres, one of authority and the other freedom, but leaves unsolved the fundamental fact, which is that of the correct relationship between the two spheres, of their legitimate measures and bounds, which becomes a constant issue of dispute. The real problem -he notes- is that of the relationship between authority and freedom.
Keywords: authority; freedom; social philosophy; authoritarian control